Minat Mengunakan Perbankan Digital Seabank: Kualitas Layanan Digital, Literasi Keuangan, dan Kemudahan Penggunaan - Rahma Suro Anjani; Makhmud Zulkifli (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
This study aims to determine the effect of digital service quality, financial literacy, and ease of use on the interest of students at Trunojoyo University, Madura, in using the digital bank SeaBank. The sampling technique used the theory of Hair et al., (2014), resulting in 126 student respondents who used SeaBank as the research sample. Data collection was carried out by distributing questionnaires with a Likert scale to measure each variable. Data analysis used multiple linear regression through the SPSS 22 (Statistical Product and Service Solution) application to determine the effect of each independent variable on interest in using SeaBank. The results showed that digital service quality had a significant effect on interest in using SeaBank with a significance value of 0.014 0.05. Financial literacy was also proven to have a significant effect on interest in using SeaBank with a significance value of 0.002 0.05. Meanwhile, ease of use had a significant effect on interest in using SeaBank with a significance value of 0.006 0.05. Simultaneously, digital service quality, financial literacy, and ease of use significantly influenced students' interest in using SeaBank's digital banking services, with a significance value of 0.000 0.05.